2015
DOI: 10.1016/j.jht.2014.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Long term functional outcomes after early childhood pollicization

Abstract: Study Design Retrospective Cohort Introduction Pollicization creates a thumb from another finger to treat hypoplasia/aplasia. Important outcomes include strength, function, dexterity, and quality of life. Purpose of the Study To evaluate mid- to long-term outcomes and examine predictors of outcome after early childhood pollicization. Methods 8 children who underwent 10 pollicizations (age at surgery ≤ 5 years) were evaluated 3 to 15 years after surgery. Anthropometrics, range of motion, and basic medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 68 publications
(82 reference statements)
1
10
0
Order By: Relevance
“…Earlier characterization of the degree of thumb hypoplasia with the use of US may also allow for more expeditious surgical interventions and potentially better outcomes. These advantages are supported by existing data from Lightdale-Miric et al, 11 who showed better long-term thumb strength after pollicization in those who received surgery at a younger age than those who had surgery at an older age.…”
Section: Discussionsupporting
confidence: 60%
“…Earlier characterization of the degree of thumb hypoplasia with the use of US may also allow for more expeditious surgical interventions and potentially better outcomes. These advantages are supported by existing data from Lightdale-Miric et al, 11 who showed better long-term thumb strength after pollicization in those who received surgery at a younger age than those who had surgery at an older age.…”
Section: Discussionsupporting
confidence: 60%
“…More recently, LED F has shown strong correlations with single limb cross-country ski distance, which one can easily argue is a dynamic measure, but showed no correlation with a static single limb balance test [ 42 ]. Additionally, the force fluctuations (e.g., RMS) during the hold phases of the SD paradigm for the upper extremity were first introduced as a method of quantifying differences in performance (i.e., sensorimotor processing) attributed to several clinical conditions [ 18 , 22 , 23 ]. Greater RMS indicates larger dynamical dispersion and suggests weaker (or looser) corrective actions by the neuromuscular controller enforcing the sustained compression.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we introduce the Lower Extremity Dexterity (LED) test, which has been proven to quantify sensorimotor processing to control instabilities while controlling for the confounding factors of strength and whole-body equilibrium [ 18 , 19 ]. The test is based on the principles of the upper extremity Strength-Dexterity (SD) test, which is a repeatable and informative paradigm that has successfully quantified differences in finger dexterity attributed to age, sex, and numerous clinical impairments [ 18 , 20 23 ]. The SD test quantifies sensorimotor processing for dynamic finger function because it is independent of strength [ 21 , 24 ] and engages distinct cortico-striatal-cerebellar networks in a context-sensitive way [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The FDT has been used in children to assess dexterity after pollicization 27 (surgically replace an absent thumb with a functional finger) 28-30 and performance in children with congenital conditions. We used the FDT to assess the unaffected hands of children ages 4 to 17 years of age with unilateral congenital differences and found that the unaffected hands were slower than the age-matched norms (unpublished).…”
Section: Dexterity Measurementmentioning
confidence: 99%